2021
DOI: 10.1021/acsami.0c20891
|View full text |Cite
|
Sign up to set email alerts
|

Non-Stoichiometry Induced Exsolution of Metal Oxide Nanoparticles via Formation of Wavy Surfaces and their Enhanced Electrocatalytic Activity: Case of Misfit Calcium Cobalt Oxide

Abstract: Most heterogeneous catalytic reactions demand high density and yet spatially separated nanoparticles that are strongly anchored on the oxide surfaces. Such nanoparticles can be deposited or synthesized in situ via nonstoichiometric methods. To date, nanoparticles have been exsolved from perovskite oxide surfaces using nonstoichiometric processes. However, the density of the space-separated nanoparticles on the oxide surfaces is still low. And less attention is paid toward the changes that happen to the host du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…Consequently, the active reaction zones on the exsolved metal–oxides are not necessarily constrained to the metal nanoparticles but can extend to the oxide surfaces . For example, Roy et al found that the catalytic activity of the exsolved calcium cobalt oxide increased after etching away the surface nanoparticles . This interesting observation indicates that the remaining host oxides after exsolution may be more catalytically active than the exsolved nanoparticles, although we must note that the etching process may introduce potential artifacts to the oxide chemistry.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Consequently, the active reaction zones on the exsolved metal–oxides are not necessarily constrained to the metal nanoparticles but can extend to the oxide surfaces . For example, Roy et al found that the catalytic activity of the exsolved calcium cobalt oxide increased after etching away the surface nanoparticles . This interesting observation indicates that the remaining host oxides after exsolution may be more catalytically active than the exsolved nanoparticles, although we must note that the etching process may introduce potential artifacts to the oxide chemistry.…”
mentioning
confidence: 95%
“…20 For example, Roy et al found that the catalytic activity of the exsolved calcium cobalt oxide increased after etching away the surface nanoparticles. 21 This interesting observation indicates that the remaining host oxides after exsolution may be more catalytically active than the exsolved nanoparticles, although we must note that the etching process may introduce potential artifacts to the oxide chemistry. The need to investigate the exsolved host oxide is further seen from recent studies where reduced or invariable performance was observed after exsolution.…”
mentioning
confidence: 97%
“…The Tafel slope will be ~120, ~40, or ~30 mV dec -1 if the rate-determining step is a Volmer, Heyrovsky, or Tafel reaction, respectively. 50 This catalyst also showcased the most facile kinetics that was corroborated by the corresponding Tafel slope. The Tafel slopes for Co0%-CuV, Co5%-CuV, Co10%-CuV, and Co20%-CuV are found to be 145 mV/dec, 113 mV/dec, 94 mV/dec, and 120 mV/dec, respectively (Figure 3b).…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 60%
“…As previously pointed out [ 43 , 44 ], secondary NiO phase could come from a small fraction of unreacted product or, more likely, from the structure ex-solution. Although no diffraction peaks of Ni metal are found, it cannot be totally discarded that the mechanism involves Ni metal ex-solution from the perovskite structure [ 55 , 56 , 57 ] and further oxidation to NiO, rather than direct NiO ex-solution [ 58 ], as described in other perovskite-related compounds. This is a consequence of the charge compensation mechanism due to the cation vacancies creation in the A-site, alternatively to the formation of larger number of oxygen vacancies and the concentration increase of trivalent nickel content from oxidation in the structure.…”
Section: Resultsmentioning
confidence: 99%